Women in Qing China - Hinsch, Bret, 1962- (Asian voices, 2022)
This groundbreaking work provides an original and deeply knowledgeable overview of Chinese women and gender relations during the Qing Dynasty (1644-1912). Bret Hinsch explores in detail the central aspects of female life in this era, including family and marriage, motherhood, political power, work, inheritance, education, religious roles, and ethics. He considers not only women's experiences but also their emotional lives and the ideals they pursued. Drawing on a wide range of Western, Japanese, and Chinese primary and secondary sources - including standard histories, poetry, prose literature, and epitaphs - Hinsch makes an important period of Chinese women's history accessible to Western readers.